Gerenciamento de projetos projeto: plano de negócio AWP-Design - Martins, Lucas Manoel (Universidade do Vale do Rio dos Sinos, 2014)
The Project, Business Plan AWP-DESIGN, aims to plan the process of opening a business of development and implementation of bespoke furniture and also planning the mapping of business process flows. The innovation in this proposal is the business opportunity to centralize development (commercial and drawing) and execution (fabrication and installation) of the products of this business (bespoke furniture) in a professional who has expertise in product development, technical knowledge and they can inclusive and perfect communication product design, thereby delivering well designed and risks of projects of very low product failure projects. The present paper presents the project management plan, which includes plans for management of integration, scope, time, cost, quality, resources, communications, risk and procurement / contracting, as good practice project management presented in the PMBOK guide 4th Edition.
Keywords: Gerenciamento de projetos; Inovação; Oportunidade; Project management; Innovation; Opportunity